2010
DOI: 10.1111/j.1539-6924.2010.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Risk Management Model Approach for Cell Therapy Manufacturing

Abstract: International regulatory authorities view risk management as an essential production need for the development of innovative, somatic cell-based therapies in regenerative medicine. The available risk management guidelines, however, provide little guidance on specific risk analysis approaches and procedures applicable in clinical cell therapy manufacturing. This raises a number of problems. Cell manufacturing is a poorly automated process, prone to operator-introduced variations, and affected by heterogeneity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…It has improved structures of health services' organizations and altered professionals' attitudes towards external and internal assessment. [9][10][11][12][13] Competent authorities, healthcare payers and hospitals devote increasing resources to quality management systems and to accreditation or certification of parts or all of their activities. Still, evidence of improved patients' outcome is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has improved structures of health services' organizations and altered professionals' attitudes towards external and internal assessment. [9][10][11][12][13] Competent authorities, healthcare payers and hospitals devote increasing resources to quality management systems and to accreditation or certification of parts or all of their activities. Still, evidence of improved patients' outcome is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…An example of adoption of a failure mode and effects analysis (FMEA) can be seen in Lopez et al [54] whereby risks were identified and prioritized and a severity/occurrence matrix was highlighted for the production of liver progenitor cells. In another study it was shown that the implementation of an FMEA/ FMECA method revealed the causality of human errors (either due to errors or inadequate training) and the subsequent introduction of 26 criticalities within GMP production of autologous chondrocyte implantation [55].…”
Section: Risk Assessment and Managementmentioning
confidence: 99%
“…c. Cell encapsulation [38,39]. f. Quality risk management approach [47]. e. Preclinical and clinical experience with mesenchymal stromal cells [44][45][46].…”
Section: Cell Therapymentioning
confidence: 99%